1985
DOI: 10.1093/oxfordjournals.molbev.a040336
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequence comparisons of the human, mouse, and rabbit immunoglobulin kappa gene.

Abstract: A comparative analysis between human, mouse, and rabbit immunoglobulin (Ig) kappa-gene DNA sequences is presented. New formulas for determining the expected length and variance of the longest block identity (a succession of matching nucleotides) between multiple random sequences are given and are used to establish statistical criteria for ascertaining the significance of block identities shared in r out of s sequences. The statistically significant block identities within and between the Ig-kappa-gene sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In studying the microbiome, no single animal model reproduces all aspects of human disease. However, phylogenetic and genetic comparisons of different mammalian genomes have clearly demonstrated that rabbits are closer to the human genome than rodents (Karlin et al, 1985 ). The rabbit microbiome is widely used to study human diseases, especially intestinal pathophysiology and periodontitis (Mapara et al, 2012 ; Jiminez et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In studying the microbiome, no single animal model reproduces all aspects of human disease. However, phylogenetic and genetic comparisons of different mammalian genomes have clearly demonstrated that rabbits are closer to the human genome than rodents (Karlin et al, 1985 ). The rabbit microbiome is widely used to study human diseases, especially intestinal pathophysiology and periodontitis (Mapara et al, 2012 ; Jiminez et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Their virtue is that they and their close relatives are local models; conservation at one genomic location is assumed not to affect conservation at distant genomic locations. In the absence of selection, local models must yield shared sequence length distributions of the form shown in Figure 8: exponential (or geometric), with a slope on a semi-log plot that depends on the details of the model [24], [39].…”
Section: Discussionmentioning
confidence: 99%